Low-Voltage Ultra-Low-Power Current Conveyor Based on Quasi-Floating Gate Transistors - Khateb, Fabian; Khatib, Nabhan; Kubanek, David (Společnost pro radioelektronické inženýrství, 2012)
The field of low-voltage low-power CMOS technology has grown rapidly in recent years; it is an essential prerequisite particularly for portable electronic equipment and implantable medical devices due to its influence on battery lifetime. Recently, significant improvements in implementing circuits working in the low-voltage low-power area have been achieved, but circuit designers face severe challenges when trying to improve or even maintain the circuit performance with reduced supply voltage. In this paper, a low-voltage ultra-low-power current conveyor second generation CCII based on quasi-floating gate transistors is presented. The proposed circuit operates at a very low supply voltage of only ±0.4 V with rail-to-rail voltage swing capability and a total quiescent power consumption of mere 9.5 µW. Further, the proposed circuit is not only able to process the AC signal as it's usual at quasi-floating gate transistors but also the DC which extends the applicability of the proposed circuit. In conclusion, an application example of the current-mode quadrature oscillator is presented. PSpice simulation results using the 0.18 µm TSMC CMOS technology are included to confirm the attractive properties of the proposed circuit.
Keywords: Quasi-floating gate MOST; low-voltage low-power MOST; CCII; quadrature oscillator